Real-world efficacy of bezlotoxumab for prevention of recurrent Clostridium difficile infection: a retrospective study of 46 patients in five university hospitals in Finland - Jarmo Oksi; A. Aalto; P. Säilä; T. Partanen; V.-J. Anttila; E. Mattila (Springer Verlag, 2022)
Reports on real-world experience on efficacy of bezlotoxumab (BEZ) has been lacking thus far. We retrospectively studied the efficacy and safety of BEZ in preventing the recurrence of Clostridium difficile infection (CDI) in five university hospitals in Finland. Seventy-three percent of our 46 patients remained free of recurrence in the following 3 months and the performance remained as 71% effective also among immunocompromised patients. In severe CDI, BEZ prevented recurrence in 63% of cases. From our study patients, 78% had three or more known risk factors for recurrence of CDI. Eight of our patients were waiting for fecal microbiota transplantation but after stopping the antibiotics that were continued to prevent recurrence of CDI and after receiving BEZ, all remained free of recurrence and did not need the procedure. Success with BEZ as an adjunctive treatment in preventing recurrence of CDI in high-risk patients may be rated as high. Among a subgroup of our patients, those already evaluated to be in need of fecal microbiota transplantation, BEZ seems to be an alternative option.